Assessing the feasibility of the socioeconomic benefits of Colophospermum mopane under climate change in north-central Namibia - Nikodemus, Andreas; Hájek, Miroslav; Bernal, Diana Carolina Huertas; WIrawan, Nia Novita; Muhoko, Edward; Nangolo, Penelao; Ndeinoma, Albertina; Shikangalah, Rosemary (Frontiers in Forests and Global Change, 2025)
Colophospermum mopane (C. mopane) is a drought-tolerant deciduous tree that provides essential ecosystem services for local communities. Despite its socioeconomic importance, the feasibility of these benefits under changing climatic conditions remains understudied, particularly in sparsely forested regions such as north-central Namibia. In this study, we assess the feasibility of C. mopane’s socioeconomic contributions in Namibia’s Kunene and Omusati regions by focusing on subsistence and commercial use. Using a semi-structured questionnaire, we collected data from local communities at four Forestry offices: Outapi, Tsandi, Opuwo, and Okahao-yielding 117 responses. We employed descriptive statistics to analyse data using IBM SPSS combined with Microsoft Excel. The results revealed that firewood was the most common product of C. mopane, primarily harvested for subsistence purposes. The products were mainly harvested from crop fields. Household income from C. mopane products ranged from <1,000 to 5,000 Namibian Dollars (NAD) per sale, with peak earnings recorded in 2019 and 2020. Key climate-related challenges affecting these benefits included floods, thunderstorms, and erratic rainfall. Respondents highlighted the need for improved wood-processing skills, better market access, and financial support to enhance the sustainability of C. mopane-based livelihoods. We recommend targeted climate adaptation strategies such as agroforestry, tree planting projects, drought-resistant crops, and community education on sustainable resource use and promoting alternative energy sources such as solar power for cooking and heating. Future studies should evaluate the effectiveness of climate adaptation and mitigation strategies in managing mopane woodlands for long-term socioeconomic resilience.